The Conflation of Health and Healthcare - Gareth Morgan (Archives of Community Medicine and Public Health - Peertechz Publications, 2015)
Health is difficult to define while healthcare relates to the various services available. Recent election campaigns within the United- Kingdom seemed to conflate the terms health and healthcare. Healthcare investment is not a guarantee of improved health, a point the general public may fully not appreciate. Recently, I attended a meeting in west Wales with a community group. Their interest in health was focused on healthcare, so we discussed an alternative model:Health determinants include alcohol intake, smoking, diet and exercise. Some of these will have underlying factors, such as poverty, low self-esteem or educational attainment.